Incidence of severe hypoglycemia in children with type 1 diabetes in the Nordic countries in the period 2008–2012: association with hemoglobin A1c and treatment modality. Issue 1 (29th May 2017) - Birkebaek, NH; Drivvoll, AK; Aakeson, K; Bjarnason, R; Johansen, A; Samuelsson, U; Skrivarhaug, T; Thorsson, AV; Svensson, J
Abstract : Objective: Treatment of type 1 diabetes has been intensified aiming at normalizing blood glucose, which may increase the risk of severe hypoglycemia (SH). We aimed to compare the incidence of SH events in the four Nordic countries Denmark, Iceland, Norway and Sweden, and to assess the influence of hemoglobin A1c (HbA1c ) and treatment modalities on the frequency of SH; particularly, to explore if a HbA1c target ≤6.7% (50 mmol/mol) is feasible. Research design and methods: Data on children below 15 years with a diabetes duration more than 1 year, registered in the national childhood diabetes databases in the four Nordic countries from 2008 to 2012, were compiled. Data completeness was more than 95%. Results: Totally 8806 (48% females) patients with 29 715 person years were included, mean age and diabetes duration were 11 years and 5.1 years, respectively. The overall rate of SH was 6.0 per 100 patient-years, and did not change during the study period. The Swedish population constantly had the lowest SH incidence while it decreased significantly in the Danish population. HbA1c decreased significantly over time (p<0.01), while the number of pump users increased (p<0.01). Stratifying for HbA1c levels showed the lowest risk of SH in patients with HbA1c ≤6.7% (≤50 mmol/mol), but in the statistical models adjusting for possible confounders the difference between the HbA1c groups disappeared. Pump users had the lowest SH risk, also after adjusting for possible confounders. Conclusions: Risk of SH differs between the Nordic countries with the lowest risk in Sweden. Pump therapy was associated with decreased risk of SH. The low HbA1c group had the same or a lower risk of SH compared with the highest HbA1c groups. A target HbA1c ≤6.7% (≤50 mmol/mol) seems achievable without increasing the risk of SH.